2023
DOI: 10.1021/acsnano.2c12747
|View full text |Cite
|
Sign up to set email alerts
|

Design of Biodegradable, Climate-Specific Packaging Materials That Sense Food Spoilage and Extend Shelf Life

Abstract: The AgriFood systems in tropical climates are under strain due to a rapid increase in human population and extreme environmental conditions that limit the efficacy of packaging technologies to extend food shelf life and guarantee food safety. To address these challenges, we rationally designed biodegradable packaging materials that sense spoilage and prevent molding. We nanofabricated the interface of 2D covalent organic frameworks (COFs) to reinforce silk fibroin (SF) and obtain biodegradable membranes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…In response to this problem, Han et al designed a COF-based embedded colorimetric sensing film to mitigate the process of grain spoilage and provide timely detection of spoilage (Figure 5b). [86] They fabricated a 2D biodegradable film, SF-COFs, by connecting ~200 nm thin films of imine-based COFs with ~50 μm silk fibroin (SF) through interface engineering. The film exhibited a ~200 % increase in Young's modulus and a ~60 % increase in ultimate tensile strength.…”
Section: Cof-based Colorimetric Sensormentioning
confidence: 99%
“…In response to this problem, Han et al designed a COF-based embedded colorimetric sensing film to mitigate the process of grain spoilage and provide timely detection of spoilage (Figure 5b). [86] They fabricated a 2D biodegradable film, SF-COFs, by connecting ~200 nm thin films of imine-based COFs with ~50 μm silk fibroin (SF) through interface engineering. The film exhibited a ~200 % increase in Young's modulus and a ~60 % increase in ultimate tensile strength.…”
Section: Cof-based Colorimetric Sensormentioning
confidence: 99%
“…Still, the reduced mechanical properties, low surface-to-volume ratio, and potential adverse sensory effects also limit further applications . Developing bio-based materials such as polymers, polysaccharides, lipids, and proteins has alleviated the dilemma of petroleum-based packaging materials that are difficult to degrade. , Researchers have looked at preparing biodegradable films using different combinations of these desirable bio-based materials with different types of antimicrobial agents to obtain antimicrobial capabilities. The migration of metal nanoparticles and metal oxides during contact with food and their toxicological potential has raised consumer safety concerns. , Although natural antimicrobial actives have certain advantages in terms of antimicrobial capacity and safety, they often have to go through complex processes during stable immobilization with different bio-based materials to achieve sufficient mechanical strength because of their unique chemical properties. …”
Section: Introductionmentioning
confidence: 99%
“…The resulting materials exhibited rapid visual changes in response to pH variations indicative of food spoilage. Such approaches that push the SF’s utility and functionalization boundaries are scientifically fascinating. , …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few novel biotechnological applications have emerged for SF, such as edible coating for perishable food preservation, smart labels, and packaging materials underscoring yet again the surprising nature of this ancient material . One study reported the elegant use of covalent organic frameworks (COFs), consisting of two-dimensional polymers with high surface area, to interface with SF films in order to produce sensing, color changing, smart labels, and packaging materials sensitive to food spoilage . The resulting materials exhibited rapid visual changes in response to pH variations indicative of food spoilage.…”
Section: Introductionmentioning
confidence: 99%